1998
DOI: 10.1128/mcb.18.3.1635
|View full text |Cite
|
Sign up to set email alerts
|

A Naturally Occurring hPMS2 Mutation Can Confer a Dominant Negative Mutator Phenotype

Abstract: Defects in mismatch repair (MMR) genes result in a mutator phenotype by inducing microsatellite instability (MI), a characteristic of hereditary nonpolyposis colorectal cancers (HNPCC) and a subset of sporadic colon tumors. Present models describing the mechanism by which germ line mutations in MMR genes predispose kindreds to HNPCC suggest a "two-hit" inactivation of both alleles of a particular MMR gene. Here we present experimental evidence that a nonsense mutation at codon 134 of the hPMS2 gene is sufficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
2
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 30 publications
3
84
2
2
Order By: Relevance
“…We were unable to demonstrate an altered methylation of the promoter region of the hMLH1 gene in the colon sample showing only the somatic mutation of the gene. However, we could not exclude that the second allele is inactivated by other mechanisms, such as large deletion or that the found mutation could be dominant-negative like the truncating mutation at codon 134 of the hPMS2 mismatch repair gene (Nicolaides et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to demonstrate an altered methylation of the promoter region of the hMLH1 gene in the colon sample showing only the somatic mutation of the gene. However, we could not exclude that the second allele is inactivated by other mechanisms, such as large deletion or that the found mutation could be dominant-negative like the truncating mutation at codon 134 of the hPMS2 mismatch repair gene (Nicolaides et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…MMR gene mutations are not always dominant by the pattern of transmission, as exemplified by PMS2 (De Rosa et al, 2000). On the cellular level, MMR gene mutations are not always recessive, but may have dominant-negative effects (Jager et al, 1997;Nicolaides et al, 1998), or be associated with haploinsufficiency (Cejka et al, 2003;Takagi et al, 2003). Furthermore, although initial studies suggested that all LOH events occurring in HNPCC tumors from MLH1 mutation carriers (6/6, 100%) affect the wt allele (Hemminki et al, 1994), a recent investigation found that up to 40% (8/20) of LOH present in HNPCC CRC may target the mutant allele (Sanchez de Abajo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Five of these genes encode proteins involved in the DNA repair pathway (Prolla et al, 1994;Drummond et al, 1995). Except in rare cases (Nicolaides et al, 1998), the mechanism leading to deficiency in DNA mismatch repair (MMR) is recessive and involves 'two hits': HNPCC patients inherit a mutated allele, then a second somatic genetic or epigenetic event occurs on the wild-type allele during the development of the tumour (Hemminki et al, 1994;Konishi et al, 1996). Through the recognition and repair of incorrectly paired nucleotides, these cancer-susceptibility genes encode cellular Extensive molecular screening for hereditary non-polyposis colorectal cancer proteins whose function is essential to the integrity of the genome and therefore belong to the 'caretakers' category (Kinzler and Vogelstein, 1997).…”
mentioning
confidence: 99%